The physiological costs of being small in a parasitic wasp - Rivero, A; West, SA (2002)
Knowledge of the relationship between body size and fitness is essential in many models of parasitoid evolutionary ecology. One clear point emerging from previous studies is that the relationship between size and fitness can depend strongly (qualitatively and quantitatively) on the environment in which it is measured. Our results show that, in the parasitoid wasp Nasonia vitripennis, the relationship between parasitoid size and fitness is strongly dependent on the nutritional status of the female; being small is more costly when food is not available. Lipid availability is the main factor mediating the relationship between size and fitness. Small females suffer disproportionately the costs of not feeding because they emerge with small lipid reserves and thus have to rely more heavily on carbohydrates for survival and reproduction. In other words, feeding is more important for small females. Our results (1) provide a physiological explanation for why laboratory estimates of the size-fitness relationship are not as steep as field estimates and (2) suggest that females are likely to show size-dependent foraging and feeding strategies.